Liprin-α proteins are master regulators of human presynapse assembly - Marcó de la Cruz, Berta; Campos, Joaquín; Molinaro, Angela; Xie, Xingqiao; Jin, Gaowei; Wei, Zhiyi; Acuna Goycolea, Claudio; Sterky, Fredrik H. (Nature neuroscience, 2024)
The formation of mammalian synapses entails the precise alignment of presynaptic release sites with postsynaptic receptors but how nascent cell-cell contacts translate into assembly of presynaptic specializations remains unclear. Guided by pioneering work in invertebrates, we hypothesized that in mammalian synapses, liprin-α proteins directly link trans-synaptic initial contacts to downstream steps. Here we show that, in human neurons lacking all four liprin-α isoforms, nascent synaptic contacts are formed but recruitment of active zone components and accumulation of synaptic vesicles is blocked, resulting in ‘empty’ boutons and loss of synaptic transmission. Interactions with presynaptic cell adhesion molecules of either the LAR-RPTP family or neurexins via CASK are required to localize liprin-α to nascent synaptic sites. Liprin-α subsequently recruits presynaptic components via a direct interaction with ELKS proteins. Thus, assembly of human presynaptic terminals is governed by a hierarchical sequence of events in which the recruitment of liprin-α proteins by presynaptic cell adhesion molecules is a critical initial step.